Meningkatkan Kualitas Belajar Siswa Sekolah Dasar dengan Menggunakan Metode Basik - Sianturi, Lisbet Rizona Br; Ritonga, Fajar Utama; Suriadi, Agus (Yayasan Literasi Sains Indonesia, 2023)
Education is one of the important aspects in Indonesia's national development. Since Indonesia's independence, the Indonesian government has been committed to expanding access and improving the quality of education throughout the region from Sabang to Merauke. This is done in order to improve the quality of human resources so that they are expected to be prospective successors of the nation. Can carry forward the ideals of the motherland. So it is necessary to further improve the quality of teaching to students. In a teaching system that tends to be monotonous and boring, it becomes a barrier to the development of students' knowledge and interest in learning. The purpose of this writing is to improve the quality of learning of elementary school students using the basik method. The practice location is on Jl. Polonia GG. B, Kec. Medan Polonia, Medan City, North Sumatra. With the focus of the research subject on grade 1 students as many as 12 students. With a period of practice for 4 months. The method used in this practice is the groupwork method proposed by Zastrow with stages consisting of: (1) Engangement, Intake and Contract, (2) assessment, (3) Planning, (4) Intervention, (5) Monitoring, (6) Evaluation, and (7) Termination. The results of this practice show an increase in interest in learning and confidence in students. This is an example of improving the quality of learning.